Efektivitas Pembelajaran al-‘Arabiyyah Bayna Yadayk terhadap Kemampuan Kalam Santriwati MTs Al-Islam: Studi Komparatif Short-Term vs Long-Term Memory - Eka Sandri Yusuf; Ratni Bt. Hj. Bahri; Raya Samir Abdulrahman Al-Rajabi (Universitas Islam Negeri Palopo, 2025)
This study aims to measure the effectiveness of al-‘Arabiyyah Bayna Yadayk learning on the speaking skills of female students at MTs Al-Islam Telaga Biru Gorontalo by comparing the results of short-term memory and long-term memory. The study uses a quantitative descriptive approach with a sample of 25 female students in grade 97. The learning process took place over one week (November 25-29, 2025) using Chapter 7 (الدِّرَاسَة) with communication-based learning activities such as hiwar, paired conversations, and picture descriptions. Speaking skills were assessed using a 1-100 scale rubric with aspects of fluency, structural accuracy, pronunciation, vocabulary, and interaction. The results showed an average short-term memory score of 90.16, with 20 students in the good category and 5 in the fair category. In the long-term memory test, the average score decreased to 83.04, with 14 students in the good category, 9 in the fair category, and 2 in the poor category. These findings indicate that al-‘Arabiyyah Bayna Yadayk learning is effective in improving speech skills in the short term, but long-term retention requires continuous practice.